If it's not what You are looking for type in the equation solver your own equation and let us solve it.
(1)=5(1)F2/19
We move all terms to the left:
(1)-(5(1)F2/19)=0
We add all the numbers together, and all the variables
-(+51F2/19)+1=0
We get rid of parentheses
-51F2/19+1=0
We multiply all the terms by the denominator
-51F2+1*19=0
We add all the numbers together, and all the variables
-51F^2+19=0
a = -51; b = 0; c = +19;
Δ = b2-4ac
Δ = 02-4·(-51)·19
Δ = 3876
The delta value is higher than zero, so the equation has two solutions
We use following formulas to calculate our solutions:$F_{1}=\frac{-b-\sqrt{\Delta}}{2a}$$F_{2}=\frac{-b+\sqrt{\Delta}}{2a}$
The end solution:
$\sqrt{\Delta}=\sqrt{3876}=\sqrt{4*969}=\sqrt{4}*\sqrt{969}=2\sqrt{969}$$F_{1}=\frac{-b-\sqrt{\Delta}}{2a}=\frac{-(0)-2\sqrt{969}}{2*-51}=\frac{0-2\sqrt{969}}{-102} =-\frac{2\sqrt{969}}{-102} =-\frac{\sqrt{969}}{-51} $$F_{2}=\frac{-b+\sqrt{\Delta}}{2a}=\frac{-(0)+2\sqrt{969}}{2*-51}=\frac{0+2\sqrt{969}}{-102} =\frac{2\sqrt{969}}{-102} =\frac{\sqrt{969}}{-51} $
| X^2-25/x+1=0 | | 8n-2n=11+13 | | F(x)=5x×2÷19 | | -4 = r−-3-3 | | 4x(-5/3)=(8x/9)+2 | | 4f-1=15 | | 2(d+13)=-12 | | 3(u+4)=18 | | 9=-11+10x | | 9x-14=9x+1 | | 4(m+10)=-4 | | 2u=-8u+10u | | 4(w-19)=-16 | | -4(m-18)=4 | | 1m+080=2m+0.75 | | x+1.1=5 | | 4(5+2y)-4=5y+3 | | 11/2=x/13 | | x+1/1/9=5 | | x+1/19=5 | | x+11/9=5 | | 15/x=60/40 | | 3x-3=2(x=4) | | M^2+22m=23 | | 9v=8v-8 | | 84=-2x-3(2x+4) | | x/12=77/132 | | 20x+2-15x=2x+1 | | 7/4m-7=3/4m-13 | | 40x+15x=900 | | 10g+5=83+g | | 3(×-5)+2=5x-7 |